PENGARUH LATAR BELAKANG PENDIDIKAN DAN PENGALAMAN MENGAJAR TERHADAP KOMPETENSI PROFESIONAL GURU SOSIOLOGI SMA DI KOTA PONTIANAK - Maryanti, Andi Iis; Zakso, Amrazi; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This thesis is entitled "The Effect of Educational Background and Teaching Experience on the Professional Competence of High School Sociology Teachers inPontianak." Sub problem research: 1) What is the effect of educational background on the professional competence of high school sociology teachers in Pontianak? 2) What is the effect of the teaching experience of teachers on the professional competence of high school sociology teachers in Pontianak? teaching experience of teachers towards the professional competence of high school Sociology teachers in Pontianak City ?.The method used is a quantitative approach. The form of this research is exposed to facto. The research subjects numbered 19 people who were high school sociology teachers in Pontianak City. The results of the analysis obtained a significant value of 0.067> 0.05 so it can be concluded that the three variables are normally distributed, the homogeneity test with a significant result of 0.264> 0.05 so that it can be concluded that the three variables are homogeneous. Hypothesis testing using the two way ANOVA (Analysis of variance) test obtained significant results of educational background and teaching experience of professional teachers by 0.038 <0.05 so it can be concluded that educational background and teaching experience have a significant effect on teacher professional competence.Keywords: Educational Background, Teaching Experience, ProfessionalTeacher Competence.